Wound Gel Formulations Containing Poloxamer 407 and Polyhexanide Have In Vitro Antimicrobial and Antibiofilm Activity Against Wound-Associated Microbial Pathogens - Jeyachchandran Visvalingam; Nandadeva Yakandawala; Suresh Regmi; Adetola Adeniji; Parveen Sharma; Miloslav Sailer (Microorganisms)
Chronic wounds are often caused or exacerbated by microbial biofilms that are highly resistant to antimicrobial treatments and that prevent healing. This study compared the antimicrobial and antibiofilm activity of nine topical wound treatments, comprising gels with different concentrations of poloxamer 407 (20–26%) and different pH levels (4–6) and containing polyhexanide (PHMB) as an antimicrobial agent; the effects of pH on wound gels containing this agent have not been previously reported. The wound gel formulations were tested against six common wound-associated microbial pathogens: Staphylococcus aureus, S. epidermidis, Pseudomonas aeruginosa, Escherichia coli, Acinetobacter baumannii, and Candida albicans. Time-kill assays were used to assess antimicrobial activity against planktonic forms of each species, and a colony biofilm model was used to assess antibiofilm activity against existing biofilms as well as inhibition of new biofilm formation. Biofilm inhibition activity was also assessed in the presence of common wound dressing materials. Wound gels with higher pH levels exhibited stronger antimicrobial activity, while poloxamer 407 concentrations >20% negatively impacted antimicrobial activity. Wound gel formulations were identified that had antimicrobial, antibiofilm, and biofilm inhibition activity against all tested species in vitro. Biofilm inhibition activity was not affected by contact with common wound dressings. Further development of these wound gels may provide a valuable new option for the treatment and prevention of chronic wounds.